PREDICTION OF THE DEFORMATION BEHAVIOR OF SAND SUBJECTED TO GENERAL CYCLIC LOADING BY THE TANGENTIAL-SUBLOADING SURFACE MODEL - H. Setouchi; K. Hashiguchi; M. Ueno (International Association of Lowland Technology, 2005)
The traditional elastoplastic constitutive equations can not generally describe the inelastic deformation considering the magnitude and the direction of the stress rate. Therefore, the stiffness is unrealistically predicted in thenonproportional loading. The tangential-subloading surface model by Hashiguchi and Tsutsumi (2001) can describe the dependence of both the magnitude and the direction of the inelastic strain rate on the stress rate. In this paper, the tangential strain rate induced by the stress rate component tangential to the yield surface is incorporated into the extended subloading surface model to describe the cyclic loading behavior. The model is applied to the prediction of the deformation behavior of sand subjected to general cyclic loading including the proportional and nonproportional loadings. The validity of the model is verified by comparing with experimental results.